Comaparative study of the response of kinematical variables from the hip and the center of mass in butterflyers - Barbosa, T.; Santos Silva, J. V.; Sousa, F.; Vilas-Boas, J. P. (2002)
The aim of this study was to compare the intracyclic variation of kinematical variables from the hip and the center of mass with the purpose to acess if the analysis of kinematical variables of the hip might replace the study of the kinematical variables of the center of mass (CM). RESULTS AND DISCUSSION Some of the correlations between the maximal vertical amplitude of displacement of the hip and the CM didn`t presents significant values. All the correlations between the horizontal velocity and horizontal acceleration of the hip and the CM were significant in all respiratory models. However, only one swimmer presented in both cases r³0.95. So, apparently, the hip do not represents properly the intracyclic variations of the kinematical variables (displacement, velocity and acceleration) of the CM.